KEMAMPUAN MEMBACA PERMULAAN ANAK USIA 5-6 TAHUN DI PAUD PERMATA UMI DESA TANJUNG PAOH - Suaini Suaini; Fadillah Fadillah; Lukmanulhakim Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe Ability to Read Early Childhood Ages 5-6 years at PAUD Permata Umi, Tanjung Paoh Village, Pinoh Utara District, Melawi Regency”. Essay. Early Childhood Education Teacher Education Study Program. Department of Education Science. Faculty of Teacher Training and Education. Tanjungpura University. Pontianak. Advisor I: Dr. Fadillah, M. Pd. Advisor II : Lukmanulhakim, ST, M. Pd. This study aims to determine the Early Reading Ability of Children aged 5-6 years in PAUD Permata Umi, Tanjung Paoh Village, Pinoh Utara District, Melawi Regency. This research uses a qualitative descriptive approach. The subjects in this study were 5 (five) children aged 5-6 years consisting of 2 (two) boys, 3 (three) girls. The data collection techniques used in this study were observation, interviews and documentation, the results of this study explained that the pre-reading abilities of children aged 5-6 years at Permata Umi PAUD were still diverse in their ability to recognize letters and the ability to arrange letters into syllables from 5 ( five) children who were taken as samples were only 1 (one) one child who could actually recognize letters and arrange letters into syllables and the other four were still lacking.Keywords: Abilit, Beginning, Reading